Being Trusted Requires Being Proactive: An Empirical Investigation of Proactive Followership - Gulnaz Shahzadi; Albert John; Imran Sharif; Hafiza Shamaila Mehnaz (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study examines the role of followers’ characteristics and proactive followership behavior in leaders’ perceptions and attitudes. We tested that politically skilled followers are proactive in their followership behavior; followers’ proactive behavior, in turn, engenders their leaders’ perception of followers’ support. Further, it is proposed that proactive followership and perceived follower support con-construct dyadic trust between leader and follower. It is a quantitative study. We conducted two self-administered surveys with a sample of 229 (leader-follower dyads) from Pakistan organizations to test the proposed relationships. Overall, we find support for the followership theory. Results suggest that followers’ political skill impacts the followers’ proactive behavior, which becomes a source to improve the leaders’ perception of followers' support. Moreover, the results confirm that the followers’ proactivity combined with perceived followers’ support and con-construct dyadic trust between followers and leaders. Very few research studies investigate leadership outcomes resulting from followers’ behavior. Understanding followers’ role in effective leadership outcomes can provide us with uniquevisions on the drivers of follower behaviors concerning their leaders. Therefore, this study investigates an essential aspect of the leadership process, currently missing in recent research.